Multilevel flow modelling as a generalized modelling technique - Bracher, Stephen (My University, 2016)
With the increasing size and complexity of industrial plants there is a growing need for modelling techniques and tools that can be used to aid the operator in the daily running of the plant. This research investigates a modelling technique, known as multilevel flow modelling (MFM) and assesses its suitability for fault diagnostic applications. A rule base for measurement validation, alarm analysis and fault diagnosis is developed which is independent of the process structure and the number of sensors used, so as not to Lose the generality of the modelling technique. A case study Shows that it is feasible to use MFM for fault diagnosis and that this technique has the flexibility to accommodate alterations.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering by course work and a project Johannesburg, 1993
Keywords: Operations research